Integrating technology into ELT - Tealdi Labrador, Antonela (2016)
Fil: The present research work intends to show the ways by which technology improves and reinforces the teaching-learning processes in a specific educational context. This is Escuela Técnica N° 1 J.B.Alberdi located in J.B. Alberdi, in the province of Tucumán, Argentina. Teachers and students are currently being exposed to vast procedural changes as regards technology. Thus, they have more accessibility to get more and more information and to keep in touch with real English-speaking communities. There was no chance of this possible interactive communication process some decades ago. The methodology of TEFL has suffered such an impact that has affected foreign language teachers, too. Due to this, they have had to enrich their teaching capacities with new and innovative approaches, strategies and techniques in order to make them up with technology. As the author Chapelle (2005) points out “[s]ince computers started to be introduced in language learning (and in education in general) people have rightly asked whether the investment we are making in these technologies gives us value for money.” Moreover, technology is actually a fruitful tool which provides a wide range of materials that help teachers to develop and improve their students’ learning skills and selfconfidence with the language they are learning and practicing. In Motteram´s words, “[t]echnology is no longer at the periphery of the ELT field, but at its centre, providing teachers with the means to enhance the teaching of languages in classrooms all over the world.” (2013:12). However, technology is a branch of knowledge that must be handled responsibly to obtain the most profitable results. The contexts in which the current research work has set forth its research denotes the existence of pros and cons when integrating and using technology in English Language teaching, particularly in English language classes at secondary schools of Concepción, Tucumán. The data obtained during the investigation supplied us with specific details which have been meaningful enough to understand the benefits and shortcomings of teaching English through technology as well as the chance to analyze and interpret the strategies, techniques and methodologies teachers employ in order to incorporate and articulate technology with the teaching of English as a foreign language at secondary schools.